State benefits and tax credits 2016: a trade union guide to in-work benefits (London, 2016)
"Trade unions can play an important role in helping their members claim the benefits to which they are entitled. Thousands of low paid workers are unaware of their entitlements and it is crucial for union reps to be aware of the latest reforms in order to give accurate initial advice. This guide is designed for that purpose. It includes details of the extensive and ongoing welfare reform changes being pursued by the Conservative government, explains how Universal Credit and the Benefit Cap work and looks at changes resulting from the new Welfare Reform and Work Act 2016. It also covers Working Tax Credit and Child Tax Credit, Child Benefit, parental pay and leave, benefits relating to housing, sickness and injury at work and the new State Pension entitlements."